Unpacking assumptions on social democratic developmental state in the Malawi Vision 2063: A critical approach - Frank Makoza (ZBW - Leibniz Information Centre for Economics, 2024)
Malawi has faced slow progress in social and economic development for the past five decades. In 2021, the country developed a national development vision to promote wealth creation and self-reliance. This study attempts to unpack the assumptions about the social democratic developmental state as a philosophical underpinning of the Malawi Vision 2063. The study analysed the Malawi Vision 2063 document using concepts from Critical Social Theory. The findings showed that the assumptions on developmental state concentrated on the role of the state, leadership, public sector involvement, and partnership discourses. The assumptions about social democratic developmental state emerged from the strategic level of government and the elite. The espoused views on the developmental state were linked with the promotion of capital and the market. Some of the statements in the thematic areas of Malawi Vision 2063 had no robust local philosophy that was well known to guide the thinking and actions of policy actors and beneficiaries (e.g. politicians, individuals, government officials and communities) in development processes and programmes. The study highlights some of the areas that require attention for the Malawi Vision 2063 to achieve successful outcomes.
Keywords: 330; Malawi Vision 2063; Development philosophy; Democratic developmental state; National development